Phylogeny of the Gondwanan beetle family Ulodidae (Tenebrionoidea) - Leschen, Richard A. B.; Escalona, Hermes E.; Elgueta, Mario (Zootaxa, 2016)
Ulodidae is a small family of saproxylic and fungus feeding beetles restricted to New Zealand, Australia, Chile and New Caledonia. The phylogeny of this family is presented for the first time, based on a cladistic analysis of 53 adult characters from 16 ulodid genera, rooted with Parahelops Waterhouse (Promecheilidae). The topology shows Arthopus Sharp at the base of the tree and confirms the placement of Meryx Latreille as a member of Ulodidae and closely related to the Chilean genus Trachyderas Philippi & Philippi. The extinct New Zealand genus Waitomophylax Leschen & Rhode was placed among a clade consisting of Brouniphylax Strand, Exohadrus Broun, and Pteroderes Germain. Two new genera and two new species are described: Ulobostrichus gen. n. (type species: Ulobostrichus monteithi sp. n.) and Ulocyphaleus gen. n. (type species: Cyphaleus valdivianus Philippi & Philippi, 1864, now U. valdivianus (Philippi & Philippi) n. comb.; U. laetus sp. n.). Dipsaconia pyritosa Pascoe is designated as the type species of Dipsaconia Pascoe and a lectotype was designated for C. valdivianus. A fully illustrated key to the genera and a checklist of the 16 genera and 42 species is included. Based on the phylogeny, the following characters are derived in the family: tuberculate body surface and the presence of scales and /or encrustations. The presence of pore-fields in the abdominal cuticle has evolved at least three times in Meryx Latreille (Australia), Syrphetodes Pascoe (New Zealand) and Trachyderastes Kaszab (New Caledonia).